PENATALAKSANAAN KOMPRES WATER TEPID SPONGE TERHADAP HIPERTERMIA PADA PASIEN KEJANG DEMAM DI IGD RS MUHAMMADIYAH PALEMBANG - Aldi Ansa (Masker Medika, 2024)
Background: Febrile seizures are seizures in children aged 6 months to 5 years that occur with an increase in body temperature of more than 38°C, which is not caused by an intracranial process. One of the nursing problems that arise in febrile seizures's case is hyperthermia. If hyperthermia is not treated properly, it can result in recurrent seizures. One of the independent nursing interventions that can be done to overcome hyperthermia is a water tepid sponge compress. Aim: The aim of this study is to implement the water tepid sponge technique in patients with febrile seizures, including assessment, diagnosis, intervention, implementation, and evaluation. Method: This study used a case study method on 2 patients with febrile seizures. Results: After the implementation of water tepid sponge compresses for 15 minutes, there was a decrease in body temperature in client An. N from 39°C to 38.1°C and in client An. B from 38.8°C to 38°C. Conclusion: Water tepid sponge compresses can be used to overcome hyperthermia problems in patients with febrile seizures. Suggestion: Further researchers can apply water tepid sponge compress management to other cases such as typhoid fever and dengue hemorrhagic fever. Keywords: Hyperthermia, Water Tepid Sponge Compresses, Febrile Seizures